Effectiveness and efficiency of SME innovation policy - James Foreman-Peck (Cardiff University, Cardiff Business School, 2012)
This paper assesses UK innovation policy impact on a large, population weighted, sample of both service and manufacturing SMEs. By focussing on self-reported innovation the study achieves a wider coverage of the effects of SME innovation policy than possible with more traditional indicators. Propensity score matching indicates that SMEs receiving UK state support for innovation were more likely to innovate than unsupported comparable enterprises. Innovating enterprises are shown to have grown significantly faster over the years 2002-4 when other growth influences are appropriately controlled. Combining these two results and comparing the outlays on SME innovation policy with the estimated effects suggests that policy was efficient as well as effective. There is evidence that SME tax credits were expensive compared with earlier support instruments. But the overall high returns estimated suggest that, even in times of public spending cuts, persisting with SME innovation policy would be prudent.
Keywords: L25; R38; 330; Innovation; State Aid; SME; Policy Evaluation